Farm records and work planning on agricultural research farms - Couper, D.C. (1995)
Research scientists must have access to field records to ensure that their experimental treatments are neither masked nor affected by previous land usage. Research fields must be identified on the ground and accurate records kept of all operations and treatments carried out. Several procedures have been developed at IITA which help to ensure accurate field records are maintained and so research accuracy is improved.